English as a second language, a second chance, or second class membership: Exploring the costs and opportunities of Latina immigrants' narratives. (March 2013) - Martin, Daniela; Daiute, Colette
Speaking a language is a socially and historically situated action through which speakers define themselves in relation to others. Using interviews collected from 15 Latina women attending an ESL program, this study examined how gender and ethnicity frame students' practices related to the study of English as a second language. Positioning analysis was used to identify the multiple roles the speakers enact in their immigrant and host communities, and describe how they strategically manage and combine these positionings to achieve multiple goals. The results show that ESL study serves disparate and sometimes contradictory purposes in the lives of immigrant students, depending on processes through which agency and vulnerability is achieved. Linking Peirce's conceptualization of student motivation as "investment" to socio-cultural theory, this study fosters a broader view of the dynamics shaping individual language use and language acquisition. By examining second language study as a cultural tool, students' motivation can be understood with a view to immigrants' social settings and power relations that define them.